The Molecular Controlled Semiconductor Resistor: A Universal Sensory Technology. Issue 5 (12th May 2014) - Capua, Eyal; Kumar, Tatikonda Anand; Tkachev, Maria; Naaman, Ron
Abstract We review some of the sensors based on the molecular control semiconductor resistor (MOCSER) technology. The technology can be applied for developing highly sensitive and selective molecular sensors that operate both in gas and in liquid environments. Specifically, we describe here a set of GaAs gas‐phase sensors based on an array constructed from several elements, each coated with a different sensing molecule. Coating the same semiconductor device with an ultrathin polymer layer also allows the use of the device in a harsh liquid environment and in performing measurements in physiological liquids. Hence, the MOCSER‐based platform opens the way for producing inexpensive, easy to use, and robust sensors for a wide variety of applications.